PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK INTERAKSI SOSIAL UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Herlina, Heni; Indryani, Indryani; Ayu Wulandari, Bunga (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to develop E-Comics media for teaching social studies on social interaction topics for junior high school students and to assess students' responses to its benefits and appeal. Using a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), the study involved seventh-grade students from SMPN 31 Muaro Jambi. Instruments used include a Likert scale questionnaire. Results indicate that the E-Comics media is feasible for use in learning, with validation scores of 85% from media experts, 92% from subject experts, and 99% from teachers. Field trials show a practical feasibility of 96%. The study is expected to contribute to the development of engaging and effective E-Comics-based learning media, offering an innovative reference for teachers to enhance student motivation and learning outcomes in junior high school.